Experimental and analytical study of dynamic properties of UGM materials containing waste rubber. Issue 130 (March 2020) - Saberian, Mohammad; Li, Jie; Nguyen, Bao Thach; Boroujeni, Mahdi
Abstract: The permanent deformation characteristic is an important material property in determining the traffic-induced load-carrying ability of unbound granular materials (UGM). Since the repeated load triaxial test (RLT) is time-consuming, complicated, and expensive, it is highly desirable that a relatively simple and quick test can be used for estimating the permanent deformation of pavement materials in the base and subbase layers. In practice, the design engineers usually rely on California bearing ratio and unconfined compression strength tests which are static tests and very much less reliable and accurate compared to dynamic tests such as the Clegg impact hammer and dynamic lightweight cone penetrometer tests. No attempt had been previously made to correlate Clegg impact value and dynamic lightweight penetration index with the permanent deformation of construction and demolition (C&D) aggregates containing crumb rubber. On the other hand, information about the dynamic behaviour of construction and demolition (C&D) materials together with waste crumb rubber, as a green and environmentally friendly pavement material, is very limited. In the current research, a serial of RLT, the Clegg impact hammer tests, and the new dynamic lightweight cone penetrometer tests were performed to evaluate the strength and stiffness of UGM incorporating different sizes/percentages of crumb rubber. The main aim of this study was to develop a simple and reliable indirect approach for estimating the permanent deformation of UGM containing crumb rubber. Based on the experimental results, it was concluded that rubber could be blended with C&D aggregates for base/subbase applications. Also, according to the analytical results, CIV and DLPI could be considered as reliable and acceptable testing methods for estimating the permanent deformation of the unbound granular materials incorporating crumb rubber for the design of flexible pavement since there was a good correlation between the testing results and the phenomenological models. Highlights: Study of the dynamic properties of unbound granular materials containing waste crumb rubber. Proposed a simple method for estimation of the permanent deformation. Strong correlations were found among the permanent deformation, DLPI, and CIV. Making new and green pavement by reusing and recycling waste materials.